Experimental and numerical analysis of bolted two plates using a developed shear theory - AY, MUSTAFA (My University, 2023)
In this study, a software has been developed for calculating static strength of bolted steel plates. This software has been developed by adding equations covering the bending moment that occurs during a tensile test as well as under real loading conditions. In order to test the accuracy of this program, 5 samples with the M6 bolt connection were prepared. In addition, the simulation result was compared with the experimental work performed with tensile tests and the finite element analysis made in Ansys
Keywords: Makina Mühendisliği; Mekanik; Sonlu Elemanlar Yöntemi; Mekanik Testler; Diğer; Mühendislik ve Teknoloji; Mechanical Engineering; Mechanical; Finite Element Methods; Mechanical Testing; Other; Engineering and Technology; Mühendislik, Bilişim ve Teknoloji (ENG); Mühendislik; MÜHENDİSLİK, MEKANİK; Engineering, Computing & Technology (ENG); ENGINEERING; ENGINEERING, MECHANICAL; Makine Mühendisliği; Hesaplamalı Mekanik; Otomotiv Mühendisliği; Fizik Bilimleri; Computational Mechanics; Automotive Engineering; Physical Sciences